Techno-economic analysis of PSA separation for hydrogen/natural gas mixtures at hydrogen refuelling stations. (15th October 2022) - Burgers, Iris; Dehdari, Leila; Xiao, Penny; Li, Kevin Gang; Goetheer, Earl; Webley, Paul
Abstract: Logistics of hydrogen is one of the bottlenecks of a hydrogen economy. In this study, a pressure swing adsorption (PSA) system is proposed for the separation of hydrogen from natural gas, co-transported in the natural gas grid. The economic feasibility of hydrogen supplied by a PSA system at a refuelling station is assessed and compared with other alternatives. The adsorbent material is key to the design of a PSA system, which determines the operation performance and cost. It is concluded that a refuelling station with hydrogen supplied by a PSA system is economically feasible. The final hydrogen price including hydrogen supply, compression, storage, and dispensing is compared with two other hydrogen supply methods: on-site electrolysis and tube-trailer transported hydrogen. Currently, PSA supplied hydrogen is a more economical option. On-site electrolysis can become a more economical option in the future with improved cell efficiencies and reduced electricity prices. Tube-trailer transported hydrogen is highly influenced by the distance travelled. The findings of this study will help with more efficient distribution of hydrogen. Highlights: A PSA process produces >99% hydrogen from natural gas/hydrogen containing 10% hydrogen. A multi-layered bed effectively removes natural gas impurities. A PSA process for a 700 kg H2/day refueller supplied from natural gas/hydrogen produces hydrogen from 12–15/kg. The PSA supplied hydrogen is cost competitive with local electrolysis supplied hydrogen.